2015
DOI: 10.5487/tr.2015.31.3.241
|View full text |Cite
|
Sign up to set email alerts
|

Furan in Thermally Processed Foods - A Review

Abstract: Furan (C4H4O) is a volatile compound formed mostly during the thermal processing of foods. The toxicity of furan has been well documented previously, and it was classified as “possible human carcinogen (Group 2B)” by the International Agency for Research on Cancer. Various pathways have been reported for the formation of furan, that is, thermal degradation and/or thermal rearrangement of carbohydrates in the presence of amino acids, thermal degradation of certain amino acids, including aspartic acid, threonine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…There are multiple pathways underlying furan and furan-derivative formation. According to Seok et al ( 2015 ), furan is formed from (i) thermal degradation or rearrangement of carbohydrates alone, or in the presence of amino acids, (ii) thermal degradation of certain amino acids, (iii) oxidation of ascorbic acid under high temperatures, and/or (iv) oxidation of polyunsaturated fatty acids and carotenoids (see Figs. 2 , 3 , 4 ).…”
Section: Volatiles Contributing To Flavourmentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple pathways underlying furan and furan-derivative formation. According to Seok et al ( 2015 ), furan is formed from (i) thermal degradation or rearrangement of carbohydrates alone, or in the presence of amino acids, (ii) thermal degradation of certain amino acids, (iii) oxidation of ascorbic acid under high temperatures, and/or (iv) oxidation of polyunsaturated fatty acids and carotenoids (see Figs. 2 , 3 , 4 ).…”
Section: Volatiles Contributing To Flavourmentioning
confidence: 99%
“…Several parameters, including fibre type, extraction (exposure) time/temperature, and the saturation of the aqueous phase in the headspace vial, affect optimal SPME conditions. Some studies focused on the selection of optimal fibers for the analysis of furan (Seok et al 2015 ) and report the best option is a carboxen/polydimethyl-siloxane (CAR/PDMS) fiber, as this showed marked advantages such as selectivity.…”
Section: Volatiles Contributing To Flavourmentioning
confidence: 99%
“…In addition, the furan in the system with sugar and sugar‐free whole milk powder was significantly higher than that of the common milk beverage system with AA, indicating that lipids have an important effect on the milk beverage system. Thermal oxidation of lipids was reported as a possible formation mechanism of furan . 4‐hydroxy‐2‐alkenals, a decomposition product of polyunsaturated fatty acids, was proposed to be a precursor of furan .…”
Section: Resultsmentioning
confidence: 86%
“…Because the protein content was constant, the furan content increased significantly (P < 0.05) with an increasing content of sugars, consistent with the previous findings indicating that sugars are one of the important precursors for furan formation. 30,31 Furan could be formed by the degradation of sugars without disrupting the intact carbon skeleton or by fragmentation proceeding via a recombination of two key intermediates, acetaldehyde and glycolaldehyde, which are decomposition products of sugars.…”
Section: Influence Of Different Primary Substrates On Furan Formationmentioning
confidence: 99%
“…Research has recently suggested the presence of undesirable or even toxic compounds in various foodstuffs [ 9 , 10 ]. Many of these compounds are created during the food production process, and particularly during thermal processing, which means that coffee substitute may also be affected.…”
Section: Introductionmentioning
confidence: 99%